Caracterização molecular e perfil de susceptibilidade e virulência de isolados clínicos de Cryptococcus spp. - Caroline Miranda de Lima (2019)
Cryptococcosis is an invasive mycosis that can affect pulmonary or cutaneous sites and, in more severe cases, can spread to the central nervous system, causing meningoencephalitis. This infection can affect immunosuppressed and immunocompetent individuals and presents a high mortality rate in patients with AIDS. Therefore, the present study carried the characterization of 60 clinical samples from the Eduardo de Menezes and Santa Casa hospitals in Belo Horizonte. The collected samples were submitted to molecular identification and analysis of susceptibility and virulence profile. We identified 54 isolates as C. neoformans genotype VNI, 4 isolates as C. deuterogattii genotype VGII and only 2 isolates as C. neoformans genotype VNII. All the isolates analyzed produced melanin and grewat 37 ° C and 39 ° C. Only three isolates did not produce phospholipase and two did not produce proteinase. Survival analysis in the Tenebrio molitor invertebrate model showed that 28 strains of C. neoformans VNI were more virulent than the H99 control isolate, that is, they killed the larvae more quickly after infection. Comparison of C. deuterogatti isolates revealed that 3 of the 4 isolates were more virulent than the ATCC24065 control strain. In relation to the antifungal susceptibility profile, all the samples analyzed were susceptible to fluconazole, voriconazole and amphotericin B. Only two isolates of C. deuterogatti presented resistance to itraconazole. The correlation with the clinical data of the patients showed that the majority of cryptococcosis patients were males, with a mean age of 41.1 years. In addition, the present study revealed that the majority of patients with cryptococcosis had some underlying disease that caused immunosuppression. Most individuals had HIV, but cases of patients with diabetes, lupus and cancer were also reported. The mortality rate among HIV patients was considered high, with a percentage of 29.8% of deaths. It is interestesting to note that the analyzed samples came from 16 cities of Minas Gerais, covering cities in the interior, metropolitan region and capital. Thus, the present study reinforces the importance of the epidemiological study of isolates of Cryptococcus, in order to know the circulating fungal species, as well as to evaluate the profile of these samples in terms of virulence and antifungal susceptibility, thus allowing a better clinical management of the patient.